Global database of diffuse riverine nitrogen and phosphorus loads and yields. (24th November 2020) - McDowell, Rich W.; Noble, Alasdair; Pletnyakov, Peter; Mosley, Luke M.
Abstract: Human activities have increased the input of nitrogen and phosphorus into riverine systems. These inputs can increase algal growth that degrades aquatic ecosystems. We constructed a global database of diffuse loads (kg) and yields (kg ha −1  yr −1 ) of dissolved and total nitrogen and phosphorus forms for 7 years (centred around 2008) in 1, 421 catchments. Yields were calculated from 640, 950 measurements that were checked, filtered and harmonized from readily available sources. We used the yield data to create a georeferenced model to calculate yields of nitrogen and phosphorus forms across 6, 020 catchments, globally. The database can be used to assess and inform policy to reduce nitrogen and phosphorus losses from land to freshwater, improve nutrient use efficiency on farms, and help calibrate global models being used to explore scenarios such as nutrient management efficiency in a changing climate. The source data and R code are provided at https://doi.org/10.25400/lincolnuninz.11894697 . Abstract : Flowchart of the steps involved in checking, filtering, georeferencing, harmonizing and analysing the data to produce a database of loads and yields for up to 1, 421 different catchments and models to estimate yields globally. Note that blue boxes are input data.